Putting Data Privacy Regulation into Action: The Differential Capabilities of Service Frontline Interfaces - Steinhoff, Lena; Martin, Kelly D. (Journal of Service Research)
Service frontline encounters between customers and service providers have been subject to fundamental changes in recent years. As two major change agents, technology infusion and data privacy regulations are inextricably linked and constitute a critical ethical and societal issue. Specifically, service frontlines—as represented by human or technological agents, or some hybrid form—rely on customer data for service provision, which subjects them to privacy regulations governing the collection, submission, access, and use of any customer data thus captured. However, scant research outlines the significant implications of evolving data privacy regulations for service frontline encounters. To advance knowledge in this domain, this research distills six key dimensions of global data privacy regulations (fairness, data limits, transparency, control, consent, and recourse). Employing an intelligences theoretical lens, the authors theorize how these dimensions might become differentially manifest across three service frontline interface types (human-based, technology-based, and hybrid). Carefully intersecting the need for varying intelligences across data privacy regulatory dimensions with the abilities of service frontline interfaces to harness each intelligence type, this study offers a novel conceptual framework that advances research and practice. Theoretical, managerial, and policy implications unfold from the proposed framework, which also can inform a future research agenda.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Hitting the Breaks While Working from Home. Changes in Taking-Breaks Behaviours During Pandemic Lockdowns - Voicu, Bogdan; Țălnar-Naghi, Dana; Neguț, Adriana; Glăvan, Eugen; Tufă, Laura; Florea, Alexandra (Sociológia - Slovak Sociological Review)
Keywords: Sociology and Political Science

A new algorithmic imaginary - Schulz, Christian (Media, Culture & Society)
The algorithmic imaginary as a theoretical concept has received increasing attention in recent years as it aims at users’ appropriation of algorithmic processes operating in opacity. But the concept originally only starts from the users’ point of view, while the processes on the platforms’ side are largely left out. In contrast, this paper argues that what is true for users is also valid for algorithmic processes and the designers behind. On the one hand, the algorithm imagines users’ future behavior via machine learning, which is supposed to predict all their future actions. On the other hand, the designers anticipate different actions that could potentially performed by users with every new implementation of features such as social media feeds. In order to bring into view this permanently reciprocal interplay coupled to the imaginary, in which not only the users are involved, I will argue for a more comprehensive and theoretically precise algorithmic imaginary referring to the theory of Cornelius Castoriadis. In such a perspective, an important contribution can be formulated for a theory of social media platforms that goes beyond praxeocentrism or structural determinism.
Keywords: Sociology and Political Science; Communication

Putting Data Privacy Regulation into Action: The Differential Capabilities of Service Frontline Interfaces - Steinhoff, Lena; Martin, Kelly D. (Journal of Service Research)
Service frontline encounters between customers and service providers have been subject to fundamental changes in recent years. As two major change agents, technology infusion and data privacy regulations are inextricably linked and constitute a critical ethical and societal issue. Specifically, service frontlines—as represented by human or technological agents, or some hybrid form—rely on customer data for service provision, which subjects them to privacy regulations governing the collection, submission, access, and use of any customer data thus captured. However, scant research outlines the significant implications of evolving data privacy regulations for service frontline encounters. To advance knowledge in this domain, this research distills six key dimensions of global data privacy regulations (fairness, data limits, transparency, control, consent, and recourse). Employing an intelligences theoretical lens, the authors theorize how these dimensions might become differentially manifest across three service frontline interface types (human-based, technology-based, and hybrid). Carefully intersecting the need for varying intelligences across data privacy regulatory dimensions with the abilities of service frontline interfaces to harness each intelligence type, this study offers a novel conceptual framework that advances research and practice. Theoretical, managerial, and policy implications unfold from the proposed framework, which also can inform a future research agenda.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

The DaimlerChrysler takeover failure revisited from a varieties-of-capitalism perspective - Riach, John Rankin Wood; Schneider, Martin (Cross Cultural and Strategic Management)
Purpose The purpose of this paper is to revisit the disastrous DaimlerChrysler AG takeover episode from 1998 to 2007 in order to arrive at a more comprehensive explanation of this and other merger and takeover failures based on institutional theory. Design/methodology/approach The case study is based on various secondary sources of information and on the insights that one of the authors gained from working for 14 years in various positions for Daimler-Benz and DaimlerChrysler. Findings DaimlerChrysler failed because top management made mistakes in trying to globalize the company. They were unable to realize possible synergies between the two companies, which brought complementary resources into the merger. Furthermore, they did not account for the institutional embeddedness of strategies when they adopted lean production globally, diffused the production system developed in Germany to other parts of the world and tried to implement a global stock enlisted in New York and Frankfurt. The underlying theoretical framework is relevant for other merger and acquisition cases. It features institutional embeddedness, path dependency and institutional arbitrage. Originality/value The paper develops an institutional perspective on DaimlerChrysler and on cross-border merger and acquisition failure more generally. The perspective is organized around the varieties-of-capitalism approach. This contribution is important because there is increasing dissatisfaction with the dominant explanation of cross-border merger and acquisition failure, which is based on the allegedly failed management of culture “clashes.”
Keywords: Organizational Behavior and Human Resource Management; Strategy and Management; Sociology and Political Science; Cultural Studies; Business and International Management

Social factors of procrastination: group work can reduce procrastination among students - Koppenborg, Markus; Klingsieck, Katrin B. (Social Psychology of Education)
Abstract Research on procrastination covers a variety of individual factors (e.g., conscientiousness) and this focus is reflected in interventions against procrastination. Less emphasis is put on situational and social factors that may help students reduce procrastination, such as social interdependence. Therefore, this study investigates the relationship between interdependence with academic procrastination and affective variables. Two vignette studies with student samples ( N 1 = 320, N 2 = 193) were conducted and data was analyzed with regression analyses and analyses of covariance. Results of both studies show lower state procrastination in group work with interdependence compared to individual work, especially in participants with high trait procrastination. This difference is more pronounced when interdependence is accompanied by an active commitment to finish the task on time. Further, interdependent group work is related to increased positive affect and decreased negative affect. The results demonstrate the relevance of situational and social factors for academic procrastination, and point toward new approaches for intervention.
Keywords: Sociology and Political Science; Developmental and Educational Psychology; Social Psychology

Constructing the “Competent” Pupil: Optimizing Human Futures Through Testing? - Dahmen, Stephan (Social Inclusion)
In the last decade, the German transition system has witnessed the large‐scale introduction of so‐called “analysis of potentials” (Potenzialanalysen) in secondary compulsory schooling. In most German Länder, 8th graders must participate in a two‐day assessment center which combines psychometric testing with observations of their social and professional competencies in pre‐specified tasks. The programmatic aim of these assessments is to “introduce pupils early to choosing a job” (Bundesministerium für Bildung und Forschung [BMBF], 2017, p. 2) as well as to enhance the propensity of pupils to “take responsibility for their own future” (BMBF, 2017, p. 9). In the context of the German school‐to‐work system, the introduction of these new forms of diagnostics bear witness to a new preventive political rationality that aims at reducing the entry age into upper secondary education, reduce the recourse to so‐called “transition measures” and optimizing transitions into an apprenticeship market that is characterized by structural inequalities and “mismatch” between pupils’ job aspirations and the offers in apprenticeship places. However, little is known on the role of competency testing devices for the construction of further trajectories and aspirations and their role in the reproduction of inequalities in transitions from school to work. Based on an in‐depth analysis of policy documents and competency profiles (the documents handed out to the pupils after undergoing testing), the article reconstructs the political rationale for the introduction of the so‐called Potenzialanalysen. Based on a Foucauldian framework, we show how pupils are constructed as “competent” subjects. We show that competency assessments are part and parcel of a political rationality that aims at the promotion of a specific (future‐oriented, optimized, self‐regulated) relation to one’s own biographical future on the side of the pupils. Our results demonstrate that competency profiles construct the process of choosing a job as an individualized project of the self and that they invisibilize structural barriers and power relations. In doing so, competency assessments potentially contribute to the reproduction of inequalities in post‐secondary education through delegating “cooling out” processes from institutional gatekeepers to the interiority of persons.
Keywords: Sociology and Political Science; Social Psychology

Как попрощаться с роботом? Исследование достижения разговорного закрытия - Егорова, Анастасия Игоревна; Klowait, Nils (The monitoring of public opinion economic&social changes)
Разговорные компьютеризированные агенты совершенствуются, развиваются и получают все более широкое распространение в различных сферах жизни. Теперь искусственный интеллект может вести беседу с человеком, используя сложные разговорные приемы и человекоподобные речевые паттерны. Например, Google Duplex, современный голосовой интерфейс, способен автономно выполнять сервисные телефонные звонки таким образом, что собеседнику не удается опознать в нем робота. С увеличением числа интерактивных коммуникаций человека и компьютера становится очевидной необходимость их изучения: каким образом они происходят, как разрешаются недоразумения и достигаются цели разговора. Статья посвящена эмпирическому изучению взаимодействия между продвинутым разговорным агентом и человеком: в рамках этнометодологии и конверсационного анализа рассмотрены последовательно разворачивающиеся, естественно возникающие речевые практики собеседников, а также порождаемые ими нормативные структуры. Материалом для анализа послужила аудиозапись телефонной беседы между Google Duplex и человеком-оператором. Исследовано, в частности, как достигается разговорное закрытие — микроструктура, требующая кооперации собеседников в организации чередования реплик. Показано, что завершение беседы происходит за счет постепенного достижения эпистемического равновесия между говорящими, несмотря на интеракционные проблемы, возникающие из-за неуместного просодического контура робота. Подчеркивается связь между институциональным контекстом взаимодействия и роботизированной природой не-человеческого собеседника. Полученные результаты закладывают основу для дальнейших исследований специфического порядка во взаимодействии человека и робота и способствуют более глубокому пониманию того, как завершается разговор в пограничных случаях. Благодарности. Статья подготовлена в сотрудничестве с Лабораторией геймификации Сбербанка. Статья подготовлена в рамках гранта, предоставленного Министерством науки и высшего образования Российской Федерации (№ соглашения о предоставлении гранта: 075-15-2020-908).
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

The Rise of Interactional Multimodality in Human-Computer Interaction - Klowait, Nils; Ерофеева, Мария Александровна (The monitoring of public opinion economic&social changes)
The field of human-computer interaction (HCI) investigates the intersection between the design of devices and users. From an early focus on interaction modeling based on psychological experiments, the field has since experienced a shift towards the study of how actual humans interact with autonomous devices. The field became conductive to ethnographic, observational and videographic studies of human-device interaction. Conversation-analytic HCI became possible. That said, this new wave of researchers was never truly able to dethrone the psychological common sense of the field. With recent developments in both the technical-sensorial capabilities and outward actuational range of embodied virtual agents, the field of HCI has once again returned to the question of the sequential unfolding of the interaction between users and intelligent agents, and the multimodal interactional repertoire that is deployed throughout. This review will highlight the situational orientation of high-impact research in the field, and relate it to the cotemporaneous development of ethnomethodological and conversation analytic frameworks. Acknowledgments. The article was prepared in the framework of a research grant funded by the Ministry of Science and Higher Education of the Russian Federation (grant ID: 075-15-2020-908). The article was prepared in cooperation with the Sber (ex. – Sberbank’s) Gamification Lab.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

The Welfare Conventions Approach: A Comparative Perspective on Social Impact Bonds - Chiapello, Eve; Knoll, Lisa (Journal of Comparative Policy Analysis: Research and Practice)
Keywords: Public Administration; Sociology and Political Science

Steuermoral in Westdeutschland nach dem Zweiten Weltkrieg. Eine diskursanalytische Rekonstruktion - Schönhärl, Korinna (Leviathan)
Die Klage über mangelnde Steuermoral ist in der aktuellen Medienberichterstattung omnipräsent, aber sie ist nicht neu: Bereits kurz nach dem Zweiten Weltkrieg wurde bemängelt, die Deutschen in den westlichen Besatzungszonen hinterzögen ihre Steuern. Verfiel die westdeutsche Steuermoral schon damals? Wie veränderte sie sich im Zeitraum zwischen 1945 und 1953? Nach einem kurzen Überblick über die Geschichte der interdisziplinären Steuermoralforschung und einigen methodischen Überlegungen, wie Historiker*innen die Entwicklung der Steuermoral qualitativ untersuchen können, wird im vorliegenden Aufsatz der Diskurs um das Steuerzahlen in der Nachkriegszeit analysiert. Durch die Analyse von Zeitungsberichten und Parlamentsdebatten werden drei unterschiedliche, konkurrierende Narrative identifiziert, die geeignet waren, ganz verschiedene »policy windows« zu öffnen. Die historische Untersuchung zeigt, dass Narrative über das (ehrliche) Steuerzahlen immer mit bestimmten politischen Interessen verknüpft sind - und dass sie deshalb auch im aktuellen Diskurs über das (ehrliche) Steuerzahlen sorgfältig analysiert werden sollten.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Socially Responsible Investment in 19th Century Greece: A Case Study of a Swiss Banker - Schönhärl, Korinna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Altruistically motivated investment has become the subject of economic, psychological and sociological research in recent years. The long tradition of ethical considerations concerning investment behavior has often been mentioned by historians but rarely investigated. This paper presents a case study of the 19th century philhellene banker Jean-Gabriel Eynard, who was philanthropically active in Greece, but also invested part of his capital on the emerging Greek market. Drawing on the methodological approach of the “sociology of morality”, this article examines how Eynard invested in Greece, which norms and values concerning investment behavior he articulated and how far they were comparable with the norms and values of today’s Socially Responsible Investment. What emerges is that the practices and the norms of Socially Responsible and Ethical Investment then and now are remarkably similar, while the “moral background” (G. Abend) has changed considerably in some, but not all points.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

The network ROI - Khan, Gohar; Mohaisen, Manar; Trier, Matthias (Internet Research)
Purpose Leveraging social action theory, social network theory and the notion of network externality, the purpose of this paper is to model two different return on investment (ROI) measures: the networked ROI which captures the network effect originating from a social media investment, and the discrete ROI which focuses social media discrete returns from individual users. Design/methodology/approach A field experiment was set up over a period of three months to test the effects of two variants of an advertisement campaign (a social vs a discrete ad) on the modeled networked and discrete ROIs. Findings The authors find that emphasizing discrete user actions leads to lower network gains, but higher monetary returns while the social action emphasis produces higher network gains, but lower monetary returns. The study further suggests that social action focus is preferable for brand promotion and engagement, whereas the discrete action focus is suitable for boosting sales and website traffic. Practical implications Several potential implications for social media researchers and marketers are also discussed. Originality/value The authors for the first time showed that that the social media returns are derived not only from individual actions taken by the user (e.g. likes and shares) but also from users’ social interdependencies and the additional exposure that results from network effects.
Keywords: Economics and Econometrics; Sociology and Political Science; Communication

Kritische Systemtheorie und Kritische Theorie sozialer Systeme. Ein Plädoyer für eine fruchtbare Unterscheidung - Alvear, Rafael; Haker, Christoph (Leviathan)
Die Systemtheorie und die Kritische Theorie sind Schulen, die Theoretikerinnen seit langem ein Zuhause bieten. In der Zeit ihres Bestehens kam es immer wieder zu Treffpunkten und Theoriekollisionen dieser beiden Traditionen des Denkens der Gesellschaft. Durch die hier entwickelte Metareflexion wird es möglich, zu analysieren, wie diese Theorietraditionen verbunden werden. Da sich die aktuelle Diskussion auf die Perspektive der Systemtheorie beschränkt, ist es notwendig, die Verbindung auch aus der Perspektive Kritischer Theorie zu debattieren. Denn erst die Unterscheidung der heute immer mehr ins Gespräch kommenden Kritischen Systemtheorie von der kaum diskutierten Kritischen Theorie sozialer Systeme macht es möglich, die volle Produktivität der Theoriekollisionen zu erkennen. Wir konzipieren unsere Metareflexion damit als eine Intervention im Sinne einer soziologischen Selbstkritik. Sie richtet sich gegen die Gefahr des theoretischen Dogmatismus und plädiert für die Öffnung der Kontingenz des eigenen Denkens der Gesellschaft.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Strategies of segregation: race, residence, and the struggle for educational equality - Pöllmann, Andreas (Ethnic and Racial Studies)
Keywords: Sociology and Political Science; Anthropology; Cultural Studies

„Rationale Fischerei“? Das Konzept des Maximum Sustainable Yield im Spannungsfeld von Ökonomie und Ökologie - Sackel, Johanna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

Social Impact Bonds und der Disput um die Wohlfahrt - Knoll, Lisa (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie)
Keywords: Sociology and Political Science; Social Psychology

Managing the Bright and Dark Sides of Status Endowment in Hierarchical Loyalty Programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)
In service industries, hierarchical loyalty programs are common relationship marketing instruments that award elevated status to customers who exceed a certain spending level (e.g., gold membership). In practice, service companies offer elevated status to some customers who do not meet the required spending level, in an attempt to profit from the profound allure of status. Relying on social psychology research and a mixed-method approach, this study analyzes the loyalty impact of status endowments, defined as awards of elevated status to customers who are not entitled to it. An exploratory qualitative study identifies customer gratitude and customer skepticism as positive and negative mediators, respectively, of customers’ attitudinal responses to endowed status. Quantitative studies—two experimental and one survey—substantiate these bright and dark sides of endowed status. The efficacy of status endowment is contingent on the context. To alleviate the dark-side effect, managers can allow target customers to actively choose whether to be endowed, especially those who are close to achieving the status already, and provide valuable preferential treatment to customers elevated by either endowment or achievement. These insights offer guidelines for whether and how to use status endowment in hierarchical loyalty programs.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Massification of Higher Education in Taiwan: Shifting Pressure from Admission to Employment - Chan, Sheng-Ju; Lin, Liang-Wen (Higher Education Policy)
Keywords: Sociology and Political Science; Education

Revenue and Profit Implications of Industrial Service Strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Journal of Service Research)
In many business markets, manufacturers seek service-led growth to secure their existing positions and continue to grow in increasingly competitive environments. Using longitudinal data from 513 German mechanical engineering companies and latent growth curve modeling, this study offers a fine-grained view of the financial performance implications of industrial service strategies. By disentangling the revenue and profit implications of industrial service strategies, findings reveal that such strategies increase both the level and the growth of manufacturing firms’ revenue streams. In contrast, they reduce the level but improve the growth of manufacturers’ profits. Results further suggest that services supporting the clients’ actions (SSC) and services supporting the supplier’s product (SSP) affect performance outcomes in different ways. SSCs directly affect revenue and profit streams. In turn, SSPs display only indirect effects on financial performance mediated through SSCs. A moderator analysis identifies two organizational contingencies that facilitate service business success: Only companies with decentralized decision-making processes and a high share of loyal customers can expect favorable financial results from industrial service strategies. In summary, this research provides significant insights and managerial guidance for turning service strategies into financial successes.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Die Bewältigung wirtschaftlicher Unsicherheit. Zum Pragmatismus der Soziologie der Konventionen - Knoll, Lisa (Berliner Journal für Soziologie)
Keywords: Sociology and Political Science